2021
DOI: 10.1371/journal.pone.0248514
|View full text |Cite
|
Sign up to set email alerts
|

Association between childhood maltreatment, psychopathology and DNA methylation of genes involved in stress regulation: Evidence from a study in Borderline Personality Disorder

Abstract: Previous research suggests that childhood maltreatment is associated with epigenetic modification of genes involved in hypothalamic-pituitary-adrenal (HPA) functioning, which could cause dysregulation of the stress response system. If pervasive, this may be associated with the development of stress-related disorder in adults, including affective disorders, anxiety disorders, post-traumatic stress disorder (PTSD) or borderline-personality disorder (BPD). The majority of studies have focused on DNA methylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
1
12
1
Order By: Relevance
“…Furthermore, lower empathic perspective-taking abilities and anxiety correlated with childhood maltreatment. Although this study does not find differences between clinical and non-clinical samples, it reveals the relationship between empathy engagement and FKBP5 DNA methylation (Flasbeck and Brüne, 2021).…”
Section: Epigenetics Changes and Psychotherapy In Bpdcontrasting
confidence: 82%
“…Furthermore, lower empathic perspective-taking abilities and anxiety correlated with childhood maltreatment. Although this study does not find differences between clinical and non-clinical samples, it reveals the relationship between empathy engagement and FKBP5 DNA methylation (Flasbeck and Brüne, 2021).…”
Section: Epigenetics Changes and Psychotherapy In Bpdcontrasting
confidence: 82%
“…Based on intergenerational observations, the long-neglected evolutionary theory of Lamarckian inheritance is currently being re-discussed. Epigenetic modifications, and the consequent regulation of the gene expression, offer a plausible mechanism for acquired biological traits and behavioral adaptations to endure throughout generations [ 30 ]. Here, the oxytocinergic system has been proposed as a possible mediator of these CM-related intergenerational transmission effects, mainly because it is a key modulator of parenting behavior, attachment, and risk of post-partum depression [ 31 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In individuals suffering from post-traumatic stress disorder, a decreased methylation has been reported compared to that of a HC group [43]. A recent study focusing on methylation levels of NR3C1-1F in patients with BPD showed lower overall methylation compared to a HC group with a negative correlation between the level of methylation and ACE [44]. Overall, the majority of those studies report small to medium effect sizes.…”
Section: Discussionmentioning
confidence: 99%